A Molecular Tuning Fork in Single‐Molecule Mechanochemical Sensing1. (8th May 2015) - Mandal, Shankar; Koirala, Deepak; Selvam, Sangeetha; Ghimire, Chiran; Mao, Hanbin
Abstract The separate arrangement of target recognition and signal transduction in conventional biosensors often compromises the real‐time response and can introduce additional noise. To address these issues, we combined analyte recognition and signal reporting by mechanochemical coupling in a single‐molecule DNA template. We incorporated a DNA hairpin as a mechanophore in the template, which, under a specific force, undergoes stochastic transitions between folded and unfolded hairpin structures (mechanoescence). Reminiscent of a tuning fork that vibrates at a fixed frequency, the device was classified as a molecular tuning fork (MTF). By monitoring the lifetime of the folded and unfolded hairpins with equal populations, we were able to differentiate between the mono‐ and bivalent binding modes during individual antibody‐antigen binding events. We anticipate these mechanospectroscopic concepts and methods will be instrumental for the development of novel bioanalyses.